Pentecostal Healing : Models in Theology and Practice - Alexander, Kimberly E., (Journal of Pentecostal Theology Supplement Series, 2006)
* WINNER, THE FOUNDATION FOR PENTECOSTAL SCHOLARSHIP 2007 AWARD OF EXCELLENCE * This detailed historical study of the formative years of Pentecostal healing shows with abundant examples how many early Pentecostals were grappling with questions of great importance for the Christian understanding of healing and its relationship to soteriology. This is essential reading for an understanding of the background to Pentecostal thinking and will inform theological reflection on issues associated with the healing ministry of the Christian church.